ANALISIS PENGUKURAN KUALITAS LAYANAN PADA JARINGAN 4G - Indra Ully Widhi Nugraha, I P; Gunantara, N; Diafari Djuni Hartawan, IGAK (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
The development of the North Denpasar area, especially the kelurahan and the Peguyangan village, has caused many migrants to come and live in the Peguyangan area and have an impact on the development of the population to increase. The population growth of the North Denpasar peguyangan region from year to year is growing very rapidly. The analysis method used in the study "Measuring Service Quality on 4G Networks" with Android-based Drive Test and Application is to analyze the measurement results with standardization or Key Performance Indicators (KPI) which are sourced from books, articles, and journals in the field using the measurement method using G-net Track Pro application to perform Drive Test and measure RSRP, RSRQ, SINR. Meanwhile, the Nperf application is used to measure Download, Upload, and Latency. Based on the results of the measurement of the signal strength in the Peguyangan Kelurahan, North Denpasar, it can be concluded, From the experiments conducted from the RSRP, RSRQ, SINR data taken in the morning and evening, in the morning the results obtained are better than in the afternoon. . The possibility of this is caused by the EU in the morning less than in the afternoon. From the experiments conducted from the Download, Upload, SINR data taken in the morning and evening, in the morning the results obtained are better than in the afternoon.